Surface Damage Coupling Mechanism of Plain Weave Art Ceramic Matrix Composites - Guangsong Li (Journal of Chemistry)
In order to solve the problem of the surface damage coupling mechanism of ceramic matrix composites, a method oriented to the damage coupling mechanism of the plain weave art ceramic matrix is proposed by the author. First, the author uses the composite material prepared by a chemical vapor infiltration process as the research object, and the damage mechanical behavior of materials under simple and complex plane stress states is studied. Second, the calculation of the mechanical property parameters of the material components and the research on the mechanical behavior of the material in-plane shear mesodamage are studied; Finally, the research on the damage coupling effect of materials under complex stress state is conducted, as well as the decoupling test research of the damage coupling effect. It is demonstrated that based on 0 and 45° off-axis tensile stress-strain behavior, a prediction model of off-axis tensile stress-strain behavior of the material was established, and the prediction results were in good agreement with the experimental results.